ASSOCIATION TYPE 2 DIABATES MELLITUS AND GASTRIC CANCER : THE SYSTEMATIC REVIEW - Talilah, Stephanie (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Gastric cancer is one of the most common types of malignant gastrointestinal tumors, and its incidence rates are climbing at an alarming rate, making it one of the most common forms. It is known as radical resection, and it is the only treatment for stomach cancer that has been demonstrated to be successful. Previous studies have established a correlation between obesity and an increased danger of acquiring cancers of the stomach and heart. Insulin resistance and the resultant hyperinsulinemia have been presented as possible causes for this syndrome. Insulin sensitivity has also been postulated. Even though obesity was not found to be directly linked to non-cardiac gastric cancer, insulin resistance may potentially play a role in the development of diabetes-related gastric cancer. This is the case despite the fact that insulin resistance may have a role in the development of diabetes-related gastric cancer. Hyperglycemia, also known as high blood sugar, can promote the growth, proliferation, invasion, and migration of cancer cells. This is especially true for cancers that affect the breast, liver, bladder, pancreas, colorectum, and endometrium. An in vitro and in vivo study discovered that it can also promote the proliferation and growth of human gastric cancer cells while also developing chemoresistance to the chemotherapeutic agent 5-fluorouracil in GCa cells. These findings were made public in the journal Cancer Research. Diabetes has been linked repeatedly to an increased likelihood of developing stomach cancer, according to research. This demonstrates the need of ensuring that the therapies used to lower the patient's blood sugar levels are carried out in the most effective manner possible.